Toleransi Beragama dalam Penafsiran - Fika Rahayu Astuti; Yuda Alfadillah; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Religious tolerance is an essential concept in religious life reflected in Islamic teachings. Islam teaches the importance of respecting and honoring differences, whether in religion, ethnicity, or culture. The concept of religious tolerance in Islam can be found in several verses of the Qur'an, which call for not imposing religion, living in harmony and peace, and helping one another regardless of differences. The freedom to choose a religion is a fundamental human right that must be respected, as each individual has the right to choose and embrace their religion according to their belief. Islam not only teaches acceptance of differences but also respects the existence of other religions, whether major or minority. Religious tolerance in Islam goes beyond merely respecting differences; it also includes the attitude of living together peacefully and helping one another, in order to create a harmonious and blessed life.